2016
DOI: 10.1088/1741-2560/13/6/066004
|View full text |Cite
|
Sign up to set email alerts
|

Identifying auditory attention with ear-EEG: cEEGrid versus high-density cap-EEG comparison

Abstract: These findings are further evidence for the feasibility of around the-ear EEG recordings and demonstrate that well described ERPs can be measured. We conclude that concealed behind-the-ear EEG recordings can be an alternative to classical cap EEG acquisition for auditory attention monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
123
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(140 citation statements)
references
References 32 publications
14
123
2
1
Order By: Relevance
“…Activation values for all vertices but the ones in the respective source region were set to zero, whereas for the vertices in a given source region we assumed a biphasic cortical activation pattern. EEG electrode positions used were based on two previous studies (Bleichner et al, 2016; Mirkovic et al, 2016), comprising 84 scalp channels arranged in an equidistant cap and 18 channels from two cEEGrids.…”
Section: Ceegrid Sensitivity—modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation values for all vertices but the ones in the respective source region were set to zero, whereas for the vertices in a given source region we assumed a biphasic cortical activation pattern. EEG electrode positions used were based on two previous studies (Bleichner et al, 2016; Mirkovic et al, 2016), comprising 84 scalp channels arranged in an equidistant cap and 18 channels from two cEEGrids.…”
Section: Ceegrid Sensitivity—modelingmentioning
confidence: 99%
“…By directly comparing simultaneously acquired scalp-EEG and ear-EEG signals, several independent laboratories have shown that ear-EEG can capture brain signals that are closely related to those recorded with scalp-EEG (Mikkelsen et al, 2015; Mirkovic et al, 2015; Bleichner et al, 2016; Zibrandtsen et al, 2016). In contrast to the classical EEG cap, ear-EEG sensors can be worn comfortably and are not more noticeable than hearing-aids or (in-ear) headphones.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings indicate that there is an optimal window-size for decoding-accuracy: shorter window sizes produce r -values that are too noisy, and longer window sizes prohibit the rapid detection of switches in attention. This problem is particularly important when using neural signals with a lower signal to noise ratio (such as around the ear [23], or in ear EEG [28]). It is possible that more elaborate decoding algorithms can be used to speed up decoding and provide a better trade-off between decoding-accuracy and transition-time [27].…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, the electrodes on the cEEGrid, developed by Debener et al [32], are located around the ear in approximately the same plane, but with larger electrode distances, compared to ear-EEG. For some paradigms it could be necessary to locate electrodes both in and around the ear to span a 3D space, and also obtain larger electrode distances to increase the amplitude of the measured ear-EEG [19]. Figure 6.4 and 6.5 generally show big differences in the potential maps for the ears, for the different orientations and locations of dipoles.…”
Section: Mapping Cortical Sources To the Earmentioning
confidence: 99%
“…20 Section 3.2 Description of the reference configurations for the real-life artifact recordings have been added. 63 Bibliography Errors in reference [19] has been corrected.…”
Section: Correctionsmentioning
confidence: 99%